Study of pH‐dependent fluorescent property of fluoroquinolone antibiotics. Issue 2 (12th October 2022) - Sajwan, Reena K.; Lakshmi, Garimella B. V. S.; Singh, Avinash K.; Solanki, Pratima R.
Abstract: Antibiotics are probably known as "wonder drugs" that inhibit bacterial growth or kill bacteria. Fluoroquinolones (FQNs) are broad‐spectrum synthetic antibiotics having excellent oral absorption and outstanding biocompatibility. It was found that some of the antibiotics themselves have a fluorescent property, and this fluorescent ability of these antibiotics has potential applications in infection diagnosis, detection of antibiotics in the environment, tracking the antibiotic uptake, and the detection of bacterial infections. In this study, we have studied the influence of pH (2–12) on fluorescence intensity, UV‐Vis absorption, and surface charge properties of fluorescent antibiotics, such as moxifloxacin, ciprofloxacin, ofloxacin, levofloxacin, and norfloxacin. The purposed study is an easy, simple way of finding the presence of antibiotics and tracking bacterial infection by changing the pH value of the medium. Abstract : The pH‐dependent fluorescence (FL) intensity of various fluoroquinolones antibiotics was studied in the pH range (4–10). At acidic pH (4), the FL intensity of ciprofloxacin and ofloxacin was enhanced, while the moxifloxacin intensity was quenched. At basic pH (10), the FL intensity shows the opposite result as that of acidic media. Apart from this, levofloxacin and norfloxacin antibiotics are more stable in the pH range of 4–10. With this study, the presence of antibiotics and their bacterial infection can easily be tracked by changing the pH value of the experimental media